APPLICATION OF INDIVISIBLE «M OUT OF N» CODES IN HIGHLY PRODUCTIVE PARALLEL COMPUTING SYSTEMS - Zhukov, I.A.; Gumenyuk, V.A. (Proceedings of National Aviation University, 2012)
The motives for beginning the automatic checkup problem in computers are considered. The “M out of N” codes applications possibilities, related to indivisible ones, are analyzed in highly productive parallel computing systems. A new scheme of computing operations organization is proposed with taking into account the peculiarities of such coding.